Transformasi Pendidikan Anak Usia Dini dalam Menyongsong Era Digital Pembelajaran - R, Nurhasanah (Jurnal Euforia, 2026)
The transformation of early childhood education (PAUD) in welcoming the digital era of learning is becoming an increasingly relevant issue amid technological advances and the need to prepare future generations who are ready to face global challenges. This article examines the application of technology in early childhood education in Bone Regency, focusing on the application of digital-based learning that can improve the quality of education and enrich children's learning experiences. This study identifies various strategies applied by PAUD educational institutions in integrating digital technology, such as the use of educational applications, digital teaching aids, and interactive learning media. In addition, this article also discusses the challenges faced by teachers and parents in adopting the technology, as well as how innovative solutions can be implemented to overcome these barriers. Through a qualitative approach, this study provides a comprehensive overview of the positive impacts and potential for further development in early childhood education in Bone Regency, leading to the strengthening of the quality of education that is more inclusive, effective, and relevant to the needs of the times.